Karya Monumental Umat Islam Dalam Ipteks - Ika Ika; Lelita Lelita; Paidatun Nisa; Tri Septiyani (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
As Muslims who are obedient in fulfilling the commandments of Islam in accordance with the Koran and hadiths, it is obligatory for Muslims to pursue knowledge as high as possible whether it is science in technology, social, and religion. Nowadays, many people only understand that it was Europeans who discovered high knowledge, but in fact it was Islamic figures at that time. Islam has experienced glory in science in the past, Islamic figures at that time really brought Islam to a very high glory. The author's background in writing this paper is to provide information about Islam as a pioneer in science at that time. In its glory civilisation Islam entered Europe, and European nations which at that time were very primitive, then helped by the arrival of these Islamic figures. That is proof of the power of science for the welfare of the people.